PROFESSIONAL ROLES OF THE HIGHER SCHOOL TEACHER IN THE FUTURE SPECIALISTS TRAINING (Educological discourse, 2019)
The article discusses the features of professional roles of a higher education teacher in the training of future specialists (using the example of a teacher of biology and human health). The features of the individual work of a teacher-tutor with a student are given; the functions of the moderator and the facilitator in the group work; working with future specialists of the teacher-curator during extracurricular time. Types of tutoring and structural elements of tutor support, moderation, facilitation, and curator functions are proposed. It is emphasized that the teacher-tutor is responsible for the level of knowledge of the student, and for the formation of his personality. The teacher-moderator carries out the process of managing the interaction in a group of students, combines the solution of issues of development of the educational group as a team, and organizes the interaction and cooperation of all participants. The teacher-facilitator stimulates the independence and responsibility of students when choosing courses, goals, and ways to achieve them when evaluating the results of their work. The teacher-curator creates external conditions and accompanies the actualization of the student’s internal reserves for full-fledged creative self-realization in all spheres of life. For the effective work of the curator it is proposed to combine the informative, organizational, communicative, administrative, creative functions. The survey data on the effectiveness of the use of new professional roles by a teacher among future specialists is indicated.